Process of conductivity in rocks - Sidorova I.P.; Saxobidinov R.I.; Golovko E.A. (E3S Web of Conferences)
In article described the program «PercolationCheck» intended for calculation of percolation (conductivity) process in rocks on the basis of raster pictures of distribution of elements in the sample, received on micro analyzer JXA-8800R JEOL. The scope of the program - research of materials - chemistry, physics of natural combinations. The program determines presence cells of percolation configurations and visually displays on the screen of computer the available in the investigated sample the clusters, their capacity, presence of one or more connecting clusters, testifying about presence’s percolation (conductivity).